Literary Criticism Psychological Approach: Nora Seed's Character in Matt Haig’s Novel The Midnight Library - Sema, Evania; Junianto, Muhammad Iqbal Fadlilah; Agus, Cecep (Universitas Pamulang, 2025)
This research aims to analyze the main character of the novel, Nora, by examining how she describes and reacts to her problems, which are influenced by her mental health, regret, and sadness. The study employs a qualitative descriptive analysis using Sigmund Freud’s psychoanalytic theory as a psychological approach to explore the development of the character's psychological state. The data for this research were collected from The Midnight Library by Matt Haig through careful and repeated reading, followed by note-taking of relevant passages. The primary data source consists of quotations from the novel, while secondary sources include theoretical references related to psychology and literature. The researcher analyzes the selected quotations in relation to Freud's theory of literary psychology. The findings reveal three defense mechanisms that significantly affect the protagonist’s personality: displacement, repression, and projection. Additionally, the study identifies three levels of consciousness—id, ego, and superego—experienced by Nora throughout the narrative. Therefore, the research highlights that practicing self-acceptance and confronting personal issues can have a profound impact on one’s life, influencing how individuals respond to challenges, go through daily life, and embrace personal growth. This can ultimately lead to a more meaningful and fulfilling future.